Material and optical properties of low-temperature NH3-free PECVD SiNx layers for photonic applications. (1st December 2016) - Domínguez Bucio, Thalía; Khokhar, Ali Z; Lacava, Cosimo; Stankovic, Stevan; Mashanovich, Goran Z; Petropoulos, Periklis; Gardes, Frederic Y
Abstract: SiN x layers intended for photonic applications are typically fabricated using LPCVD and PECVD. These techniques rely on high-temperature processing (>400 °C) to obtain low propagation losses. An alternative version of PECVD SiN x layers deposited at temperatures below 400 °C with a recipe that does not use ammonia (NH3 -free PECVD) was previously demonstrated to be a good option to fabricate strip waveguides with propagation losses <3 dB cm −1 . We have conducted a systematic investigation of the influence of the deposition parameters on the material and optical properties of NH3 -free PECVD SiN x layers fabricated at 350 °C using a design of experiments methodology. In particular, this paper discusses the effect of the SiH4 flow, RF power, chamber pressure and substrate on the structure, uniformity, roughness, deposition rate, refractive index, chemical composition, bond structure and H content of NH3 -free PECVD SiN x layers. The results show that the properties and the propagation losses of the studied SiN x layers depend entirely on their compositional N/Si ratio, which is in fact the only parameter that can be directly tuned using the deposition parameters along with the film uniformity and deposition rate. These observations provide the means to optimise the propagation losses of the layers for photonic applications through the deposition parameters. In fact, we have been able to fabricate SiN x waveguides with H content <20%, good uniformity and propagation losses of 1.5 dB cm −1 at 1550 nm and <1 dB cm −1 at 1310 nm. As a result, this study can potentially help optimise the properties of the studied SiN x layers for different applications.